Taxonomic revision of the “Pierella lamia species group” (Lepidoptera: Nymphalidae: Satyrinae) with descriptions of four new species from Brazil - Zacca, Thamara; Siewert, Ricardo R.; Casagrande, Mirna M.; Mielke, Olaf H. H.; Paluch, Márlon (Zootaxa, 2016)
Four new species of Pierella Westwood, 1851 from Brazil are described: P. angeloi Zacca, Siewert & Mielke sp. nov. from Maranhão, P. kesselringi Zacca, Siewert & Paluch sp. nov. from Paraíba, Pernambuco, Alagoas and Sergipe, P. nice Zacca, Siewert & Paluch sp. nov. from Bahia and P. keithbrowni Siewert, Zacca & Casagrande sp. nov. from Bahia, Espírito Santo, Rio de Janeiro, São Paulo, Paraná and Santa Catarina. Additionally, P. chalybaea Godman, 1905 stat. rest. and P. boliviana F.M. Brown, 1948 stat. nov. are recognized as valid species and not as subspecies of P. lamia (Sulzer, 1776), while P. l. colombiana Constantino & Salazar, 2007 syn. nov. is synonymized to the former. Lectotype and paralectotype of Papilio dyndimene Cramer, 1779 (a synonym of Pierella lamia) and Pierella chalybaea Godman, 1905 stat. rest. are designated. Habitus and illustrations of male and female genitalia are provided for all species, as well as a geographical distribution map.